Experimental Research on Destruction Characteristics of Mud Inrush on Tunnel in Argillaceous Fault Fracture Zone - Yang, Teng; Zhang, Qingsong; Zhang, Xiao; Wang, Deming (IOP conference series. Earth and environmental science, 2020)
The argillaceous fault fracture zone is a special area which bears the most concentrated stress when it forms and develops. Therefore, the tunnel under construction is subject to serious water and mud inrush when excavated through this area. In order to explore the destruction characteristics of mud inrush, a large-scale three-dimensional geological model test was carried out, which overcomes the "black box" problem of the traditional test, and a cone-shaped and parabolic body model were proposed to depict the shape of soil disturbance. In addition, the evolution law of displacement field inside medium was studied and the change regulation of actual disaster influence area also was been revealed. Finally, the tunnel mud inrush mechanics were revealed according to destroyed characteristics. As the results showed, the location of the initial mud inrush occurred at the spandrel of the tunnel face, the displacement of soil near the location of mud inrush increased with proceeding time, but there was a sudden saltation of the increasing rate when the disaster occurred. Besides, the shape of surface subsidence above the location of the inrush gradually transferred from "W" to "V" in the process of mud inrush. With the increase of the number of mud inrush, the soil disturbance develops from the local to the whole. When the local disturbance occurs, the soil form is cone, while when the whole disturbance occurs, the soil form is parabola. In addition, it is found that soil displacement is related to the seepage pressure under different disturbance modes. Finally, the conclusion of the model test may shed light on the catastrophic process and evolution law of the mud inrush in fault fracture zone. which has certain guidance and reference significance for the prevention of mud inrush in similar projects.